A scratch-resistant spray-free polypropylene composite material and preparation method thereof
By using scale glass powder and microcrystalline mica-loaded toner in glass fiber reinforced polypropylene to form a glass-based composite pigment with a sheet structure and combined with flat glass fiber, the pigment dispersion and floating fiber problems are solved, and the brightness and scratch resistance of the material are improved.
Patent Information
- Application Number
- CN202411184242.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-27
AI Technical Summary
When preparing spray-free polypropylene composites, the pigment dispersion is difficult, the surface floating fiber is blooming, the toner adhesion is low, the brightness is difficult to improve, and the wear resistance is poor, and scratches are easy to occur.
Scale glass powder and microcrystalline mica loaded toner are used to form a glass-based composite pigment with a sheet structure, and combined with chopped flat glass fibers, and melt-extruded and granulated by a co-direction twin-screw extruder to obtain scratch-resistant spray-free polypropylene composite material.
It achieves good dispersion of pigments, improves the brightness and scratch resistance of the material, solves the problems of toner adhesion and floating fibers, and enhances the stiffness and strength of the material.
Smart Images

Figure CN118931039B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic modification, and in particular to a scratch-resistant spray-free polypropylene composite material and a preparation method thereof. Background Art
[0002] Polypropylene is a polymer material with excellent properties. Various parts produced by injection molding are widely used in the shells of automobiles, instruments, home appliances, daily necessities, toys, washing machines, etc. In particular, the rapid development of new energy vehicles requires a large number of lightweight alternatives. Polypropylene is used in large quantities in automobile bumpers, dashboards, interior panels, door handles, and intake manifolds, cooling fans, fan covers, etc. around the engine.
[0003] By adding glass fiber to reinforce and modify polypropylene, the obtained glass fiber reinforced polypropylene composite material has excellent strength, rigidity, high temperature resistance and wear resistance, and is very suitable for manufacturing automotive parts. However, the appearance of polypropylene injection molded products reinforced with glass fiber is prone to floating fibers, and the appearance is difficult to meet the appearance requirements of the products. It is usually necessary to beautify the appearance by spraying paint, electroplating and other methods. Although the post-spraying method makes polypropylene products more beautiful, it also makes it difficult for the material to meet the requirements of low odor and low emission for automotive interior decoration. In addition, the post-sprayed plastic products are not wear-resistant, prone to scratches, and easy to cause the coating to fall off in high temperature, corrosion and other environments. Furthermore, the plastic spraying process inevitably has a negative impact on the environment and increases the manufacturing cost.
[0004] Spray-free plastics are made by adding pigments and pearlescent powder to plastic raw materials, and can obtain the desired bright color of plastic products during injection molding. In addition to the automotive field, spray-free plastics are widely used in home appliances such as air-conditioning panels, refrigerator panels, and rice cooker panels. Even if the surface is repeatedly rubbed, the product still maintains its original color, which can maintain the stability of the appearance color of the product for a longer time, greatly improving the texture of the product. Spray-free plastics simplify the production process, eliminate the painting process, effectively avoid VOC emissions generated during the painting and painting process, reduce pollution to the environment, and conform to the trend of green environmental protection.
[0005] According to the prior art, Chinese invention patent publication number CN117844166 A discloses a composition for spray-free plastic products, a spray-free plastic product and a preparation method thereof. The raw material composition of this technology uses 80-85 parts by weight of ABS, 4-6 parts by weight of SEBS, 4-6 parts by weight of POE, and 5-8 parts by weight of modified SiO2. The weight ratio of hydrophilic SiO2 to hydrophobic SiO2 in the modified SiO2 is 8:2; Chinese invention patent publication number CN118027555 A discloses a high-gloss scratch-resistant spray-free polypropylene material and its preparation method and application. The preparation raw materials include: 15-80 parts of high-flow homopolymer polypropylene, 10-30 parts of high-rigidity homopolymer polypropylene, 10-30 parts of high-flow copolymer polypropylene, 1-20 parts of rigidity modifier, 0.1-5 parts of scratch-resistant agent, 0.02-2 parts of surface-treated metal pigment, 0.1-0.5 parts of antioxidant, and 0.1-0.55 parts of lubricant. This technology enables the polypropylene material to have excellent mechanical properties, high gloss and scratch resistance through the effect and synergistic effect of the rigidity modifier in the material.
[0006] Spray-free plastics have higher requirements for color dispersion, glossiness, durability, and wear resistance. Especially in glass fiber reinforced polypropylene systems, the adhesion of pigments is more difficult, the wear resistance is worse, and the gloss and dispersion of pigments are not good, which leads to the aggregation of pigments and easily produces injection flow marks and blooming, which directly affects the appearance of the product, and seriously limits the use of glass fiber reinforced polypropylene as a spray-free material. Summary of the invention
[0007] Glass fiber reinforced polypropylene composite materials have good strength, but due to the presence of glass fiber, it is more difficult to disperse the pigment when preparing spray-free polypropylene, the surface of the injection molded parts is floating and flowery, the adhesion of the color powder is low, and it is more difficult to improve the brightness. In view of the above technical problems, the present invention proposes a scratch-resistant spray-free polypropylene composite material and a preparation method.
[0008] In order to achieve the above object, the present invention adopts the following specific technical solutions:
[0009] A scratch-resistant spray-free polypropylene composite material, characterized by comprising the following raw materials in parts by weight: 50-60 parts of polypropylene, 15-35 parts of chopped glass fibers, 3-10 parts of glass-based composite pigments, 1-3 parts of glass microbeads, 0.5-0.8 parts of silicone powder, 0.5-1.5 parts of a compatibilizer, and 0.2-0.4 parts of an antioxidant;
[0010] Among them, the glass-based composite pigment is made of flake glass powder, microcrystalline muscovite, color powder, dispersing aid, and coupling agent ground and compounded; the chopped glass fiber is alkali-free flat glass fiber chopped strands pre-impregnated with silane coupling agent, with a single fiber width of 15-25μm, a thickness of 3-7μm, and a fiber length of 1-2mm.
[0011] The polypropylene is homopolymer polypropylene with a melt index of 10-15 g / 10 min (230° C., 2.16 kg), which ensures high rigidity and facilitates the dispersion of pigments.
[0012] The glass-based composite pigment is prepared by grinding and compounding flake glass powder, microcrystalline muscovite, color powder, dispersing aid and coupling agent according to a mass ratio of 30-50:10-20:5-15:0.2-0.3:0.3-0.5.
[0013] Further preferably, the color powder is matched according to color requirements, and the particularly preferred basic color powder is at least one of nano alumina, nano precipitated barium sulfate, nano zinc sulfide, nano zinc oxide, carbon black, graphite, iron black, iron red, titanium yellow, bismuth yellow, titanium nickel yellow, titanium chrome brown, cobalt blue, cobalt green, iron zinc chrome brown, and metal aluminum powder.
[0014] Further preferably, the flake glass powder is selected to have a thickness of ≤5μm and a diameter-to-thickness ratio of ≥20. The flake glass powder is ground and compounded with color powder, and the color powder is mixed between the scales. Since the flake glass powder is light-transmissive and easy to slide, it is used in polypropylene and not only has bright color, but also has excellent dispersion, wear resistance, and does not fade. The microcrystalline muscovite has a thickness of ≤1μm and a thin flake structure. Under the irradiation of light, it exhibits a silky luster and halo, and can greatly improve the brightness of polypropylene after being compounded with pigments.
[0015] Further preferably, the dispersing aid is one or more of zinc stearate, erucic acid amide, polyethylene wax, pentaerythritol stearate, and ethylene bis fatty acid amide.
[0016] Further preferably, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.
[0017] The glass microbeads have a particle size of 5-13 μm, are spherical particles, have a smooth surface, and have a low oil absorption value, and can effectively promote the flow and brightness of materials, increase wear resistance, and reduce injection flow marks.
[0018] The compatibilizer preferably contains a polymer of glycidyl methacrylate (GMA), and at least one of Arkema's AX8700, AX8750, AX8820, AX8840, AX8900, and AX8930 is particularly preferred. GMA can be grafted onto the polymer due to the presence of highly active acrylate double bonds, and can be used as a toughening and compatibilizer to enhance the combination of glass fiber, glass-based composite pigment and polypropylene, and effectively prevent color fading and exposure of glass fiber.
[0019] The antioxidant is a hindered phenol main antioxidant 1010 and a phosphite auxiliary antioxidant 168 used in combination.
[0020] The present invention further provides a method for preparing a scratch-resistant spray-free polypropylene composite material, characterized in that it comprises the following steps:
[0021] S1: Dry-grinding and compounding flake glass powder, microcrystalline muscovite, color powder, dispersing aid, and coupling agent according to a mass ratio of 30-50:10-20:5-15:0.2-0.3:0.3-0.5, so that the color powder is compounded with the flake glass powder and microcrystalline muscovite having a sheet structure to obtain a glass-based composite pigment;
[0022] S2: Add 50-60 parts of polypropylene, 15-35 parts of chopped glass fibers, 3-10 parts of glass-based composite pigments, 1-3 parts of glass beads, 0.5-0.8 parts of silicone powder, 0.5-1.5 parts of compatibilizer, and 0.2-0.4 parts of antioxidant into a mixer according to weight parts, mix well, and transport to a silo for standby use;
[0023] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: zone 1 120-140°C; zone 2 150-160°C; zone 3 170-180°C; zone 4 190-200°C; zone 5 210-220°C, zone 6 230-235°C; zone 7 220-230°C; zone 8 200-210°C; zone 9 180-190°C; zone 10 160-170°C; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling, and screening.
[0024] The dry grinding compound described in step S1 can be selected from but not limited to the following grinding methods: high-speed airflow impact compound, airflow vortex micro-powder grinding compound, and stirred mill grinding compound. In the stirred grinding compound, 1-3mm aluminum zirconium balls are used as grinding media. During the grinding compound process, the shearing and impact effects generated by mechanical forces reduce the surface energy of the powder, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a sheet structure to form a glass-based composite pigment.
[0025] The mixer described in step S1 is a V-type mixer, which is conducive to fully mixing the staple fibers with the glass-based composite pigment, silicone powder, compatibilizer, and antioxidant.
[0026] Step S3 uses chain conveying and air cooling to avoid negative effects such as water absorption of materials caused by water cooling treatment.
[0027] Glass fiber reinforced polypropylene has greatly expanded its application field due to its good wear resistance, creep resistance, fatigue resistance, corrosion resistance, electrical insulation, and rigidity / specific strength. The present invention uses flake glass powder and microcrystalline white mica to load color powder, and the composite color powder with sheet structure is used in the glass fiber reinforced polypropylene system to form a good color and bright effect; glass flakes and microcrystalline white mica mixed with color powder are arranged in parallel and overlapped in the resin, which can fill the gaps at the interface of plastic products and increase the surface hardness of the plastic, which is not only bright but also wear-resistant and does not fade; at the same time, the composite color powder with sheet structure is well combined with flat glass fiber, which solves the problem of color powder adhesion and floating fiber problem, and the flat glass fiber can significantly improve the rigidity, strength and scratch resistance of polypropylene.
[0028] The present invention has the following beneficial effects due to the adoption of the above technical solution:
[0029] 1. The present invention utilizes flake glass powder and microcrystalline muscovite to load color powder to obtain a glass-based composite pigment with a flake structure. The composite pigment with a flake structure forms a good brightening effect in a glass fiber reinforced polypropylene system.
[0030] 2. The present invention uses a sheet-structured composite color powder that is well combined with flat glass fiber, solving the problem that the color powder is not easy to adhere and fade; the flat glass fiber can significantly improve the stiffness, strength and scratch resistance of polypropylene.
[0031] 3. The technical solution of the present invention has wide color adaptability and can prepare spray-free polypropylene composite materials with different color requirements by matching basic color powders.
[0032] 4. The preparation of the present invention is short, the process is easy to control, the manufacturing equipment is mature, and it is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to further clarify the technical implementation scheme of the present invention, the present invention is further described below in conjunction with the accompanying drawings:
[0034] Figure 1 This is a schematic diagram of the preparation process of a scratch-resistant spray-free polypropylene composite material of the present invention, wherein 1-grinding to prepare glass-based composite pigment; 2-V-type mixer mixing; 3-co-rotating twin-screw extruder melt extrusion granulation.
[0035] Figure 2This is a picture of an injection molded sample of the porcelain white scratch-resistant spray-free polypropylene composite material prepared in Example 1.
[0036] Figure 3 This is a picture of an injection molded sample of the bright blue scratch-resistant spray-free polypropylene composite material prepared in Example 2. DETAILED DESCRIPTION
[0037] The following implementation scheme is intended to further describe the implementation process of the technical content of the present invention, rather than limiting the scope of protection of the claims of the present invention. For those embodiments that do not specify specific conditions, they are all carried out according to the process conditions of conventional conditions, such as the screw thread combination to ensure good shearing and dispersion of short fibers. Those skilled in the art can make similar improvements without violating the connotation of the present invention. However, the implementation schemes that follow the technical ideas of the present invention obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present invention.
[0038] Selection of special raw materials of the present invention:
[0039] Flake glass powder: thickness ≤5μm, diameter-to-thickness ratio ≥20.
[0040] Microcrystalline muscovite: thickness ≤1μm.
[0041] E-glass flat chopped strands: width 15-25μm, thickness 3-7μm, fiber length 1-2mm.
[0042] Glass beads particle size: 5-13μm.
[0043] Example 1
[0044] S1: adding flake glass powder, microcrystalline white mica, nano alumina, nano zinc sulfide, zinc stearate, ethylene bis fatty acid amide, and silane coupling agent to a stirred mill in a mass ratio of 50:10:5:5:0.2:0.1:0.3 for grinding and compounding, using 1-3 mm aluminum zirconium balls as grinding media, and reducing the surface energy of the powder due to the shearing and impact effects generated by mechanical forces during the grinding and compounding process, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a flake structure to form a glass-based composite pigment;
[0045] S2: Add 60 parts of homopolypropylene with a melt index of 15g / 10min, 25 parts of alkali-free flat glass fiber chopped strands, 8 parts of glass-based composite pigments, 2 parts of glass beads, 0.5 parts of silicone powder, 1 part of compatibilizer AX8930, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0046] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0047] The scratch-resistant spray-free polypropylene composite material particles were injection molded in an injection molding machine. The temperature of the injection melting section was set at 240°C, the nozzle temperature was set at 260°C, and the mold temperature was set at 85°C. The surface of the injection molded sample was bright porcelain white, see attached Figure 2 .
[0048] Example 2
[0049] S1: adding flake glass powder, microcrystalline white mica, cobalt blue, metallic aluminum powder, zinc stearate, ethylene bis fatty acid amide, and silane coupling agent in a mass ratio of 50:10:6:1:0.2:0.1:0.3 to a vortex airflow mill for grinding and compounding. During the grinding and compounding process, the shearing and impact effects of mechanical forces reduce the surface energy of the powder, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a sheet structure to form a glass-based composite pigment;
[0050] S2: Add 60 parts of homopolypropylene with a melt index of 15g / 10min, 25 parts of alkali-free flat glass fiber chopped strands, 3 parts of glass-based composite pigments, 2 parts of glass beads, 0.5 parts of silicone powder, 1 part of compatibilizer AX8930, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0051] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0052] The scratch-resistant spray-free polypropylene composite material particles were injection molded in an injection molding machine. The temperature of the injection melting section was set at 240°C, the nozzle temperature was set at 260°C, and the mold temperature was set at 85°C. The surface of the injection molded sample was bright blue, see attached Figure 3 .
[0053] Example 3
[0054] S1: adding flake glass powder, microcrystalline white mica, Cabot carbon black, 1000 mesh flake graphite, pentaerythritol stearate, and aluminate coupling agent in a mass ratio of 50:10:2:8:0.3:0.3 to a high-speed airflow impact machine for grinding and compounding. During the grinding and compounding process, the shearing and impact effects of mechanical forces reduce the surface energy of the powder, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a flake structure to form a glass-based composite pigment;
[0055] S2: Add 55 parts of homopolypropylene with a melt index of 15g / 10min, 30 parts of alkali-free flat glass fiber chopped strands, 5 parts of glass-based composite pigments, 2 parts of glass beads, 0.5 parts of silicone powder, 1.5 parts of compatibilizer AX8900, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0056] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0057] The scratch-resistant spray-free polypropylene composite material particles are injection molded in an injection molding machine. The temperature of the injection melting section is set at 240°C, the nozzle temperature is set at 260°C, the mold temperature is set at 85°C, and the surface of the injection molded sample is bright black.
[0058] Example 4
[0059] S1: Add flake glass powder, microcrystalline white mica, titanium yellow, cobalt green, erucic acid amide, and silane coupling agent in a mass ratio of 40:20:5:2:0.3:0.3 to a stirred mill for grinding and compounding, and use 1-3 mm aluminum zirconium balls as grinding media. During the grinding and compounding process, the shearing and impact effects generated by mechanical forces reduce the surface energy of the powder, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a sheet structure to form a glass-based composite pigment;
[0060] S2: Add 60 parts of homopolypropylene with a melt index of 15g / 10min, 20 parts of alkali-free flat glass fiber chopped strands, 4 parts of glass-based composite pigments, 2 parts of glass microbeads, 0.5 parts of silicone powder, 1 part of compatibilizer AX8750, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0061] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0062] The scratch-resistant spray-free polypropylene composite material particles are injection molded in an injection molding machine. The temperature of the injection melting section is set at 240°C, the nozzle temperature is set at 260°C, and the mold temperature is set at 85°C. The surface of the injection molded sample is bright olive green.
[0063] Comparative Example 1
[0064] S1: Add microcrystalline white mica, nano-alumina, nano-zinc sulfide, zinc stearate, ethylene bis fatty acid amide, and silane coupling agent in a mass ratio of 60:5:5:0.2:0.1:0.3 into a stirred mill for grinding and compounding, and use 1-3 mm aluminum zirconium balls as grinding media. During the grinding and compounding process, the shearing and impact effects generated by mechanical forces reduce the surface energy of the powder, thereby forming physical adsorption, so that the color powder is loaded on the flake glass powder and microcrystalline white mica with a sheet structure to form a composite pigment;
[0065] S2: Add 60 parts of homopolypropylene with a melt index of 15g / 10min, 25 parts of alkali-free flat glass fiber chopped strands, 8 parts of composite pigments, 2 parts of glass beads, 0.5 parts of silicone powder, 1 part of compatibilizer AX8930, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0066] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0067] Comparative Example 2
[0068] According to the technical solution of Example 1, the alkali-free flat glass fiber chopped strands were replaced with conventional round strands (diameter 13-17 μm, length 1-2 mm) during mixing.
[0069] Comparative Example 3
[0070] S1: Evenly mix nano-alumina, nano-zinc sulfide, zinc stearate, ethylenebisfatty acid amide, and silane coupling agent in a mass ratio of 5:5:0.2:0.1:0.3 to form a composite pigment;
[0071] S2: Add 60 parts of homopolypropylene with a melt index of 15g / 10min, 25 parts of glass fiber (round wire with a diameter of 13-17μm and a length of 1-2mm), 1.2 parts of composite pigment, 2 parts of glass microbeads, 0.5 parts of silicone powder, 1 part of compatibilizer AX8930, 0.2 parts of hindered phenol primary antioxidant 1010, and 0.1 parts of phosphite secondary antioxidant 168 into a V-type mixer according to weight parts, mix well, and transport to the silo for standby use;
[0072] S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: 120°C for zone 1; 150°C for zone 2; 170°C for zone 3; 190°C for zone 4; 210°C for zone 5, 230°C for zone 6; 220°C for zone 7; 200°C for zone 8; 190°C for zone 9; 170°C for zone 10; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling and screening.
[0073] Gloss terminology: Gloss is the ratio of the specular reflectivity of the sample plastic panel to the specular emissivity of the reference surface under the same conditions at a specified incident angle (this test uses a 20° incident angle). It is expressed as a percentage, omitting the percentage sign, and expressed in gloss units. Gloss can reflect the mirror effect of the material through comparison.
[0074] The panel was injection molded under the same injection molding process conditions, and the gloss of the plastic panel was measured at an angle of 20° with reference to GB / T 8807 "Test method for mirror gloss of plastics", which was used to relatively and quantitatively measure the brightness and surface quality of spray-free plastics, as shown in Table 1.
[0075] The sample was injection molded into a panel, and a metal scraper was used to scratch multiple groups of mutually perpendicular scratches on the surface of the plastic panel with a force of 15N. The scratch resistance was measured based on the scratches, as shown in Table 1.
[0076] Table 1:
[0077] sample Appearance Average gloss Scratch resistance (15N scratch) Example 1 No floating fibers, bright, no flow marks 89.3 No obvious scratches Example 2 No floating fibers, bright, no flow marks 87.8 No obvious scratches Example 3 No floating fibers, bright, no flow marks 89.7 No obvious scratches Example 4 No floating fibers, bright, no flow marks 83.3 No obvious scratches Comparative Example 1 No floating fibers, poor gloss, no flow marks 78.1 No obvious scratches Comparative Example 2 No floating fibers, bright, with flow marks 79.4 Scratches, scratches but no damage Comparative Example 3 There are floating fibers, poor gloss, and flow marks 72.1 Scratches, scratches, and damage
[0078] The above specific examples are used to illustrate the principle and positive effects of the present invention. Obviously, the present invention obtains a glass-based composite pigment with a sheet structure by loading color powder with flake glass powder and microcrystalline muscovite, and forms a good brightening effect in the glass fiber reinforced polypropylene system, and is suitable for a variety of color powder composite color matching; furthermore, the composite color powder with a sheet structure is well combined with the flat glass fiber, which solves the problem that the color powder is not easy to adhere and fade, and cooperates with the flat glass fiber to significantly improve the stiffness, strength and scratch resistance of polypropylene, and its technical effect is obvious. The above embodiments and comparative examples also illustrate this technical effect.
Claims
1. A scratch-resistant spray-free polypropylene composite material, characterized in that The raw material composition includes the following parts by weight: 50-60 parts of polypropylene, 15-35 parts of chopped glass fibers, 3-10 parts of glass-based composite pigments, 1-3 parts of glass microbeads, 0.5-0.8 parts of silicone powder, 0.5-1.5 parts of compatibilizer, and 0.2-0.4 parts of antioxidant; The glass-based composite pigment is prepared by grinding and compounding flake glass powder, microcrystalline white mica, color powder, dispersing aid, and coupling agent according to a mass ratio of 30-50:10-20:5-15:0.2-0.3:0.3-0.5, wherein the flake glass powder has a thickness of ≤5 μm and a diameter-to-thickness ratio of ≥20; the microcrystalline white mica has a thickness of ≤1 μm; The chopped glass fibers are alkali-free flat glass fiber chopped strands pre-impregnated with a silane coupling agent, with a single fiber width of 15-25 μm, a thickness of 3-7 μm, and a fiber length of 1-2 mm; The compatibilizer is a polymer containing glycidyl methacrylate.
2. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The polypropylene is homopolymer polypropylene with a melt index of 10-15 g / 10 min (230° C., 2.16 kg).
3. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The toner is matched according to color requirements, and the selected basic toner is at least one of nano alumina, nano precipitated barium sulfate, nano zinc sulfide, nano zinc oxide, carbon black, graphite, iron black, iron red, titanium yellow, bismuth yellow, titanium nickel yellow, titanium chrome brown, cobalt blue, cobalt green, iron zinc chrome brown, and metal aluminum powder.
4. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The dispersing aid is one or more of zinc stearate, erucic acid amide, polyethylene wax, pentaerythritol stearate, and ethylene bis fatty acid amide.
5. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The coupling agent is at least one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.
6. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The particle size of the glass microbeads is 5-13 μm.
7. The scratch-resistant spray-free polypropylene composite material according to claim 1, characterized in that: The antioxidant is a hindered phenol main antioxidant 1010 and a phosphite auxiliary antioxidant 168 used in a mass ratio of 2:
1.
8. A method for preparing the scratch-resistant spray-free polypropylene composite material according to any one of claims 1 to 7, characterized in that: The steps include: S1: dry-grinding and compounding the flake glass powder, microcrystalline muscovite, color powder, dispersing aid, and coupling agent in a mass ratio of 30-50:10-20:5-15:0.2-0.3:0.3-0.5, so that the color powder is compounded with the flake glass powder and microcrystalline muscovite having a sheet structure to obtain a glass-based composite pigment; the dry-grinding and compounding is selected from a high-speed airflow impact compounding, an airflow vortex micro-powder machine grinding compounding, and a stirred mill grinding compounding; when the stirred mill grinding and compounding is selected, aluminum zirconium balls with a particle size of 1-3 mm are used as grinding media; S2: Add 50-60 parts of polypropylene, 15-35 parts of chopped glass fibers, 3-10 parts of glass-based composite pigments, 1-3 parts of glass beads, 0.5-0.8 parts of silicone powder, 0.5-1.5 parts of compatibilizer, and 0.2-0.4 parts of antioxidant into a mixer according to weight parts, mix well, and transport to a silo for standby use; S3: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw with a length-to-diameter ratio greater than 48:1; the extrusion temperature of each zone is controlled as follows: zone 1 120-140°C; zone 2 150-160°C; zone 3 170-180°C; zone 4 190-200°C; zone 5 210-220°C; zone 6 230-235°C; zone 7 220-230°C; zone 8 200-210°C; zone 9 180-190°C; zone 10 160-170°C; and a scratch-resistant, spray-free polypropylene composite material is obtained by screw shearing and dispersion, melt extrusion drawing, chain conveying, air cooling, and screening.
Citation Information
Patent Citations
Composition for spraying-free plastic product, spraying-free plastic product and preparation method of spraying-free plastic product
CN117844166A
High-gloss scratch-resistant spraying-free polypropylene material as well as preparation method and application thereof
CN118027555A
Scratch-resistant silver-texture spraying-free polypropylene composite and preparation method thereof
CN108047627A
Spraying-free high-gloss plastic for household appliances and preparation method of plastic
CN110591277A